PENGARUH PERMAINAN TRADISIONAL KUCING DAN TIKUS TERHADAP KEMAMPUAN KERJA SAMA ANAK USIA 5-6 TAHUN DI TK TUNAS HARAPAN KABUPATEN KETAPANG KALIMANTAN BARAT - Natalia Kemba, Lidia; Lukmanulhakim, Lukmanulhakim; Amalia, Annisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the traditional “cat and mouse” game on the cooperative skills of 5-6-year-old children at Tunas Harapan Kindergarten in Ketapang Regency, West Kalimantan. The background of this study is the importance of cooperative skills as an aspect of early childhood social development that can be fostered through fun and interactive play activities. This study employed a quantitative approach using a pre-experimental method and a one-group pretest-posttest design. The study subjects consisted of 7 children from Group B, selected via purposive sampling. Data collection was conducted through observation and documentation using an observation sheet covering five indicators: active participation, shared goals, role division, adherence to rules, and organized social interaction. Data analysis involved quantitative descriptive analysis, the Shapiro-Wilk normality test, and a paired-sample t-test. The results indicated an improvement in the children’s cooperation skills, with the pretest mean score of 67.14 increasing to 82.86 on the posttest. The t-test results showed a significant value (p < 0.05), so it can be concluded that the traditional cat-and-mouse game has a positive and significant effect on the cooperation skills of children aged 5-6 years. Thus, this game is effective as an active, contextual learning strategy that aligns with the characteristics of children.